Advances in Cryptology - EUROCRYPT 2009 28th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Cologne, Germany, April 26-30, 2009. Proceedings - Joux, Antoine. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 28th Annual International Conference on the Theory and Applications of Cryptographic Techniques, EUROCRYPT 2009, held in Cologne, Germany, in April 2009. The 33 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from 148 submissions. The papers address all current foundational, theoretical and research aspects of cryptology, cryptography, and cryptanalysis as well as advanced applications. The papers are organized in topical sections on security, proofs, and models, hash cryptanalysis, group and broadcast encryption, cryptosystems, cryptanalysis, side channels, curves, and randomness.